2020
DOI: 10.1128/mbio.02352-20
|View full text |Cite
|
Sign up to set email alerts
|

A New Subclass of Exoribonuclease-Resistant RNA Found in Multiple Genera of Flaviviridae

Abstract: Viruses have developed innovative strategies to exploit the cellular machinery and overcome the antiviral defenses of the host, often using specifically structured RNA elements. Examples are found in the Flavivirus genus (in the family Flaviviridae), where during flaviviral infection, pathogenic subgenomic flaviviral RNAs (sfRNAs) accumulate in the cell. These sfRNAs are formed when a host cell 5′ to 3′ exoribonuclease degrades the viral genomic RNA but is blocked by an exoribonuclease-resistant RNA structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 68 publications
(122 reference statements)
0
23
0
Order By: Relevance
“…Some authors have contested this division, arguing that the tertiary interactions of the class 2 xrRNAs structures can be used to predict those of class 1 [ 103 ]. However, the results of a recent study combining bioinformatics, biochemical and structural analysis suggest the further redefinition of class 1 into two subclasses: 1a and 1b [ 107 ]. Although full consensus is yet to be reached, most authors agree that the use of the two-class classification system aids for a more comprehensive understanding of xrRNAs and provides a tool for searching for new xrRNAs in different viral systems.…”
Section: Subgenomic Flavivirus Rnasmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have contested this division, arguing that the tertiary interactions of the class 2 xrRNAs structures can be used to predict those of class 1 [ 103 ]. However, the results of a recent study combining bioinformatics, biochemical and structural analysis suggest the further redefinition of class 1 into two subclasses: 1a and 1b [ 107 ]. Although full consensus is yet to be reached, most authors agree that the use of the two-class classification system aids for a more comprehensive understanding of xrRNAs and provides a tool for searching for new xrRNAs in different viral systems.…”
Section: Subgenomic Flavivirus Rnasmentioning
confidence: 99%
“…A clear example of how different primary and secondary structures can lead to the same 3D xrRNA has been reported in the divergent flavivirus Tamana bat virus (TABV) [ 30 , 107 , 109 , 110 ]. X-ray crystallization studies have shown that while the ring-like structure of the xrRNA is preserved across TABV and other flaviviruses, significant variations occur in the corresponding nucleotide sequences and secondary structural elements [ 107 , 110 ]. One major difference resides in the shortening of the stems that form the ring-like structure.…”
Section: Subgenomic Flavivirus Rnasmentioning
confidence: 99%
See 3 more Smart Citations